KEMAMPUAN BERAKAR CANGKOK PINUS BOCOR GETAH PADA VARIASI JENIS MEDIA CANGKOK DAN DOSIS IBA DI BATURRADEN, JAWA TENGAH - Hapsari, Marya Tiara; Widiyatno, W (Forestry Faculty of Hasanuddin University, 2023)
Pine resin product optimization was carried out through various breeding activities, not only by developing a high-sap-producing clone selection but also by developing propagation techniques. Vegetative propagation on the superior genotyping provides a large genetic gain because of its wide variation ratio produced in one selection rotation. Vegetative propagation for Pinus mercusii is commonly done by air layering, shoot cutting, and cutting that produces callous (BAJOS). This study aims to determine the effect of various media and dosages of IBA on the number and length of pine air layering roots in West Banyumas. The plants aged two years from superior clones were air layered on the branch end using two different media, namely topsoil, and cocopeat. They sprayed with IBA solution on the chipped area at dosages of 0 ppm, 500 ppm, and 1000 ppm. The parameter observed is rooting percentages, number, and length of primer and secondary root. The pine air layer on the cocopeat medium performs significantly on rooting percentages compared to topsoil. Some primer roots on 0 ppm of IBA have the best performance compared to others. The 500 and 1000 ppm IBA cannot give significance to the independent variable.